Implementation and Challenges Faced by Madrasah Teachers Through the Deep Learning Approach in Arabic Language Learning - HM, Ahmad Syagif (Fitrah, 2025)
This study aims to examine the implementation of deep learning approaches in Arabic language learning and identify the challenges faced by teachers in madrasahs. This study uses a qualitative approach with Arabic teachers at MTsN 1 Kota Bima as the research subjects. Data collection techniques include observation, in-depth interviews, and documentation. The results of the data analysis show that the application of deep learning in madrasahs is carried out through several strategies, including: institutional commitment in the formulation of regulations and the provision of supporting infrastructure, integration of the approach with the Merdeka Curriculum, implementation of meaningful and enjoyable learning, and contextualization of material relevant to students' lives. In addition, collaboration between teachers and students is also key to creating a deep learning process. However, the implementation of this approach is not without challenges, such as teachers' limited understanding of deep learning concepts due to a lack of training, students' heterogeneous backgrounds, and limited time and learning environments that do not support active Arabic language practice. These findings recommend the importance of intensive training for teachers and madrasah policy support in creating a transformative and sustainable learning ecosystem.